PROGRAM KESISWAAN DALAM MENAIKAN PRESTASI SISWA - Mu'izzu, Muhammad Abdul; Salim, Hakimuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This article discusses the management program management program in shaping student morals that runs at SMP Muhammadiyah 5 Surakarta. Student management is an important aspect of the entire process of student management. Activities that are planned and endeavored as well as continuous coaching of the entire process of students so that students have morals. To the entire process of students so that students have good morals. The purpose of writing this article is to find out about the student affairs program in raising student achievement at SMP Muhammadiyah 5 Surakarta. This article uses research with qualitative methods, as well as a field study approach approach with data collection techniques in the form of observation, interviews, and documentation. Documentation and data analysis in the form of data reduction, data presentation, and conclusion drawing. Conclusion drawing. The results of this study, that the habituation of positive things and positive things and karimah character in the school environment is realized by the strategy of strategies such as smiles, greetings, greetings, politeness and courtesy, habituation of worship, as well as the appearance process in the school environment. Worship, as well as the performance process in shaping morals, is always monitored and evaluated. and evaluation.